Identyfikacja czynników wpływających na kształt infrastruktury informatycznej przedsiębiorstw partnerskich - Turek, Tomasz (Identifying Factors Shaping Information Technology Infrastructure of the Partnership Businesses, 2007)
Operating business entities in the environment which is difficult to predict results in greater interest in various forms of business partnership and co-operation amongst the entities. When it comes to the systems of partnership businesses, understanding the environment, within which a given organization operates, substantially changes. Apart from the micro- and macroenvironment, there emerges new subenvironment comprised of entities composing the business partnership. The article discusses the key factors shaping the information technology infrastructure of the co-operating businesses as well as where they originate from.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 266-274